2019
DOI: 10.1002/anie.201901536
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Ionene Polymers into Efficient Cathode Interlayers with Pendent Fullerenes

Abstract: A new and highly efficient cathode interlayer material for organic photovoltaics (OPVs) was produced by integrating C60 fullerene monomers into ionene polymers. The power of these novel “C60‐ionenes” for interface modification enables the use of numerous high work‐function metals (e.g., silver, copper, and gold) as the cathode in efficient OPV devices. C60‐ionene boosted power conversion efficiencies (PCEs) of solar cells, fabricated with silver cathodes, from 2.79 % to 10.51 % for devices with a fullerene acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 29 publications
(28 reference statements)
0
41
0
Order By: Relevance
“…Besides, interface engineering through CIL plays a significant role in the improvement of OSCs devices. Recently, it has been demonstrated that interface engineering, primarily through inserting CIL between the electrode and photoactive layer could significantly enhance the performance of OSCs 89–91 . To achieve high efficiency, solution processible CIL should fulfill the following basic essential requirements: (1) To make ohmic contact, it should be able to make a proper energy level alignment with a photoactive layer for efficient electron transport and collection.…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
“…Besides, interface engineering through CIL plays a significant role in the improvement of OSCs devices. Recently, it has been demonstrated that interface engineering, primarily through inserting CIL between the electrode and photoactive layer could significantly enhance the performance of OSCs 89–91 . To achieve high efficiency, solution processible CIL should fulfill the following basic essential requirements: (1) To make ohmic contact, it should be able to make a proper energy level alignment with a photoactive layer for efficient electron transport and collection.…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
“…Therefore, one of the key challenges to settle this problem is to develop stable interfacial materials with balanced charge transfer and energy level matching. [17][18][19] Many solution-processed small molecule and polymer cathode interfacial materials have been reported, including conjugated (PDINO, PFN)/non-conjugated and neutral/charged materials. [20][21][22][23] Among them, PFN-based polymers are limited in further processing considerations due to strict thin thickness (5-10 nm).…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully demonstrated that some alcohol/water soluble organic cathode interlayer materials (CIMs) can provide an energy-level alignment at the electrode interface, as well as an interfacial dipole for an ohmic contact 19,[30][31][32][33][34][35] . As a typical example, we reported such effective CIMs, PDIN bearing amino group and PDINO bearing amino N-oxide group on perylenediimide (PDI) 36 .…”
mentioning
confidence: 99%
“…A solution is to design CIMs with highly polar groups to increase its dipole moment and thus to increase its ability in WF tunability. However, this approach is constrained by the intrinsic high surface tension of the CIMs bearing the polar group, which harms its solution deposition on active layer, and could result in poor contact between the CIM and the active layer 26,[30][31][32][33][34] . It is well-known that the physically poor contact hampers electron collection by the electrode, which is one of the reasons for the low fill factor (FF) in OSCs (ref.…”
mentioning
confidence: 99%